Antithrombotic Treatment in Lower Extremity Peripheral Arterial Disease - Anders Gottsäter (Frontiers in Cardiovascular Medicine, 2021)
Lower extremity arteries might be affected by atherosclerotic peripheral arterial disease (PAD), or by embolization causing ischaemic symptoms. Patients with PAD often have widespread atherosclerosis, and progression of PAD is associated with increased risk for both other cardiovascular events and cardiovascular mortality. Peripheral arterial disease patients should therefore be offered both non-pharmacological and pharmacological secondary prevention to reduce the risk for future ischemic arterial complications. This review is focussed on the rationale for recommendations on antiplatelet and anticoagulant treatment in PAD. Asymptomatic PAD does not warrant either anticoagulant or antiplatelet treatment, whereas patients with ischaemic lower extremity symptoms such as intermittent claudication or critical limb ischemia caused by atherosclerosis should be offered platelet antiaggregation with either low dose aspirin or clopidogrel. Combined treatment with aspirin and low-dose of the direct oral anticoagulant (DOAC) rivaroxaban should be considered and weighed against bleeding risk in symptomatic PAD patients considered at high risk for recurrent ischaemic events and in patients having undergone endovascular or open surgical intervention for PAD. Patiens with cardiogenic embolization to lower extremity arteries should be recommended anticoagulant treatment with either one of the DOACs (apixaban, dabigatran, edoxaban, and rivaroxaban) or warfarin.